The Effect Of Compensation And Leadership Style On Employee Performance At CV. Giri Putra In The City Of Tasikmalaya - Aeni, Rani Nur; Karmila, Mila; Pauzy, Depy Muhamad (Journal of Management, Economic, and Accounting, 2023)
The purpose of this study is to determine the effect of compensation and leadership style on employee performance at CV. Giri Putra in Tasikmalaya City. The research method used is a quantitative method with a census approach to 45 respondents who are employees of CV. Giri Putra. The analytical method used is multiple linear regression analysis. The result of hypothesis testing found that Compensation and Leadership Style simultaneously have a significant effect on Employee Performance at CV. Giri Putra in Tasikmalaya City. Partial Compensation has no significants effect on Employee Performance at CV. Giri Putra in Tasikmalaya City and Leadership Style partially have a significant effect on Employee Performance at CV. Giri Putra in Tasikmalaya City.